A new method to characterize sludge stickiness during drying: Effects of sludge temperature and calcium oxide (CaO) on stickiness. Issue 9 (11th June 2020) - Deng, Wenyi; Xiao, Jiamin; Lai, Zhicheng; Su, Yaxin
Abstract: Stickiness is a phenomenon widely observed in drying practices of sewage sludge. This work is aimed at demonstrating the effects of sludge temperature (30–70 °C) and calcium oxide (CaO) on the stickiness of two municipal sewage sludges, based on a newly designed device which can conveniently and systematically determine the temperature-dependent variables of tensile stress (adhesion), shear stress (adhesion) and compression stress (cohesion), respectively. The results indicated that both sludges showed the highest stickiness in the moisture range of 0.43–1.50 kg H2 O kg −1 DS (dried sludge). In sticky region, the compression stress was an order of magnitude higher than the shear stress, while the shear stress was about 1–4 times higher than the tensile stress. Furthermore, CaO addition (3 wt.%) led to the increase of the tensile stress, shear stress and compression stress, partially owing to the increased release of organic components (protein, polysaccharides (PSC) and total organic carbon (TOC)) from sludge. However, despite of the increased release of organic components, marked decrease of the above-mentioned stresses was observed when sludge temperature increased from 30 °C to 70 °C, indicating that the temperature-induced changes of sludge rigidity and liquid tension played more important roles in sludge stickiness than organics release. The results of the analysis of variance (ANOVA) indicated that the moisture content of the sewage sludge showed the most significant influence on the tensile stress, shear stress and compression stress, compared with that of the temperature and CaO.